IMPLEMENTASI METODE ELBOW DAN K-MEANS CLUSTERING UNTUK MENGETAHUI KAPASITAS SOLAR PANEL - Sebatubun, Maria Mediatrix; Prayitna, Adiyuda (Informasi Interaktif : Jurnal Informatika dan Teknologi Informasi, 2023)
According to electricity growth data, electricity consumption in Indonesia continues to increase. In 2015 electricity consumption was 910 kilowatt hours (kWh)/capita, then increased to 1,084 kWh/capita in 2019. Currently, Indonesia still relies on thermal power plants whose main energy sources come from fuel oil, gas and coal. With increasing electricity consumption, it is necessary to increase generating capacity. Indonesia has the potential to develop new and renewable energy, because Indonesia is located in the tropics where the sun shines almost all year round. This study aims to determine how much power capacity is obtained by solar panels, so it can meet the demand when it is cloudy and raining for a relatively long time. The data used is data collected for 2 days with an interval of collection every 15 seconds. The research was carried out by preprocessing, then looking for k cluster values using the Elbow method, after that the clustering stage used the k-means method. The results showed that the largest capacity obtained by solar panels was around 60 Watts, while the smallest capacity was around 17 Watts.